Caregivers to older adults require support: A scoping review of their priorities. (17th October 2022) - Hall, Steven; Rohatinsky, Noelle; Holtslander, Lorraine; Peacock, Shelley
Abstract: The vast majority of older adults who are chronically ill rely on informal caregivers for support. Caregivers often require additional support to facilitate their role. To the best of our knowledge, there has yet to be a collation of caregiver‐identified priorities for support. Using existing research, this scoping review provides a comprehensive picture of what caregivers have indicated as priorities for support. Arksey and O′Malley's scoping review framework guides this review. We searched MEDLINE, CINAHL and PsycINFO databases on July 2, 2021. We selected databases based on their relevance to nursing, health and social science. Inclusion criteria were peer‐reviewed research of any design, a sample population of caregivers to older adults (>55 years), manuscripts published in English and the priorities for caregiver support identified by caregivers themselves. We screened a total of 3591 records, and 33 articles met the inclusion criteria. These studies were from geographic settings across the globe and used various quantitative, qualitative and mixed‐method study designs. In our synthesis, we quantified the identified priorities within the studies using coding and content analysis. We present the following list of caregiver‐identified priorities: (1) orientation to the caregiving role; (2) self‐care and respite; (3) adapting healthcare; (4) improved supports; (5) information needs; (6) access to resources; (7) financial assistance. Policymakers, healthcare professionals and non‐profit organisations can use evidence from this review to guide decisions when developing support services and interventions for caregivers.